The complete edition Software engineering for real-time systems : a software engineering perspective toward designing real-time systems - Cooling, J. E. (Packt Publishing, 2019)
With this book, you will learn the fundamentals of developing a real-time system. The book relies heavily on diagrams to make the learning process easier and more interesting for you.